Trajectories of total and central adiposity throughout adolescence and cardiometabolic factors in early adulthood - Araujo, J (2016)
BACKGROUND/OBJECTIVES: Our aim was to identify trajectories of total and central adiposity from 13 to 21 years, and to investigate how adiposity changes at different phases of adolescence relate to adulthood cardiovascular risk factors. SUBJECTS/METHODS: This study included participants from a population-based cohort (EPITeen), Portugal. Body mass index (BMI) and waist circumference (WC) were measured at 13, 17 and 21 years, and sex- and age-specific z-scores were calculated. Adiposity trajectories were identified using mixture growth models (BMI, n=2901; WC, n=2898). Cardiovascular risk factors were evaluated at 21 years (n=1763): systolic (SBP) and diastolic blood pressure (DBP), insulin resistance (HOMA-IR), triglycerides and cholesterol. Association of trajectory, and changes in adiposity z-scores with each cardiovascular risk factor was estimated by linear regression models. RESULTS: 'Normal', 'high, declining' and 'high, increasing' trajectories were identified in both sexes. 'High, increasing' BMI trajectory was associated with less favorable cardiovascular risk profile at 21 years in both sexes, whereas 'high, declining' presented a more favorable profile, similar to 'normal' trajectory in females. In addition, BMI increases between 13-17 years and 17-21 years were associated with increases in systolic and diastolic blood pressure, and insulin resistance, but more strongly for the later period. For every standard deviation (s.d.) increase in BMI between 17-21 years, mean SBP increased by 1.99 mmHg (95% confidence interval (CI): 1.01; 2.97) for females and 3.83 mmHg (2.67; 4.98) for males; the respective increase was 1.56 mmHg (0.72; 2.40) and 2.80 mmHg (1.97; 3.64) for DBP and 0.27 (0.21; 0.32) and 0.30 (0.24; 0.36) for HOMA-IR (log-transformed). Similar results were found for WC. CONCLUSIONS: Increases in adiposity, particularly from late adolescence-to-young adulthood, were associated with unfavorable cardiovascular profile in early adulthood. A benefit on the cardiovascular risk profile for participants in the declining adiposity trajectory was observed.